PENGARUH VARIASI PRODUK DAN FASILITAS TERHADAP MINAT BELI ULANG KONSUMEN PADA ILO PETA KOTA BIMA - ningsih, marhei; Amirulmukminin, Amirulmukminin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
AbstractThis associative research was conducted to see whether there was an effect of variations in products and facilities on consumer repurchase interest at the Café Ilo Peta Kota Bima. The instruments were arranged using a liker scale which distributed 96 samples from an unknown population. The questionnaire was tested for validity and reliability, and the results were all statements made were valid and reliable, so the questionnaire was worthy of being distributed for data collection tools. From the results of data analysis using the SPSS version 20 application, partially Product Variations have an effect on the Consumer Buyback Interest in Café Ilo Map of the City of Bima, it is marked by the value of Sig = 0,000 <α = 0.05. The same thing also happened at the facility, that the Facilitator also influenced the consumer's repurchase interest in the Café Ilo Map of the City of Bima because of the value of Sig = 0.04 <α = 0.05. Seen from the Simultaneous relationship, Product and Facility Variations together affect the repurchase interest in Bima Café Ilo Map because the Sig value is smaller than α or standard error (0,000 <0.05).